MY SAY: R& D key to highincome and sustainable economy - Abd Razak, Dzulkifli (2010)
Now that the New Economic Model (NEM) is open for discussion, it is plain to see that the strengthening of R&D cannot be overemphasised. For this to happen, a thorough review of R&D as a new imperative must take into consideration ways to create a new national talent base. This includes a more flexible and autonomous environment that is conducive to innovation and creativity, preferably backed by a strong research culture and funding at all levels of education.